Evaluation of indwelling pH monitoring technologies and growing strategies for beef cattle - Weir, Colton (My University, 2025)
A series of experiments were conducted to evaluate different technologies currently utilized within the cattle industry to continuously and remotely measure ruminal pH, limit-feeding high energy rations on newly received cattle performance and digestion. Subacute ruminal acidosis (SARA) is the predominant digestive disorder affecting feedlot cattle. Despite the prevalence and economic loss, there is still debate about the exact timing, pH range, and time spend under that curve that induces SARA. Historically, measuring ruminal pH has been conducted through digesta samples via cannulation, stomach tube, or aspiration of the ventral sac. A disadvantage to all these methods is the invasiveness and disruption of normal cattle behavior to collect samples. Therefore, in Exp 1. we evaluated two different indwelling monitoring boli that continuously measure ruminal pH. We compared using smaXtec boli (SMAX; smaXtec Inc., Graz, Austria), Moonsyst boli (MOON; Moonsyst International, Kinsale, Republic of Ireland), and a handheld pH meter (METER; PH8500 pH/mV Meter, Apera, Columbus, OH) over 126 d in vivo, ex vivo in known standards, and during an ex vivo acidosis challenge. Eight ruminally cannulated crossbred heifers were utilized in a complete randomized design through 6-consecutive 21-d periods. Ruminal pH measurements obtained from MOON were lesser (P ≤ 0.01) than METER in every period. As time progressed the difference between the two became larger ∼ 84 to 126 d (treatment × period, P < 0.01). Conversely, measurements of pH with SMAX were greater (P < 0.01) than METER from periods 1 to 3 and 6. In a known pH standard of 7, MOON again yielded measurements lesser than 7 and SMAX yield measurements greater 7 (treatment × period, P < 0.01). However, in a standard at lower pH of 4, MOON and SMAX measurements were not different (P ≥ 0.13) from pH 4 until period 6 (treatment × period, P = 0.02). During the acidosis challenge, the degree of change in pH before and after the addition of vinegar was measured using MOON, SMAX, and METER. The change in pH obtained using METER was considered the true change in pH. MOON yielded measurements similar (P = 0.36) to METER while SMAX measurements were greater (P < 0.01) compared with METER. In Exp 2. we evaluated the effects of increasing dietary energy while restricting intake on growth performance, digestion, and fermentation characteristics in growing beef heifers. In Exp 2.a 70-day growing study was conducted to determine the effects of energy concentration and dry matter intake on growth performance, digestion and fermentation characteristics of newly received growing beef cattle. A total of 392 crossbred heifers (initial bodyweight = 274 ± 26 kg). Heifers were blocked by weight (4) and assigned to 12-13 head pens; pens were randomly assigned to 1 of 4 dietary treatments. Experimental treatments included a high-roughage diet fed for ad libitum intake (AL) or a limit-fed high-energy diet fed at 75% (LIM75), LIM80 (80), or 85% (LIM85) of AL intake within block. Treatments were designed to equalize energy intake between calves assigned to AL and LIM75. In Exp 3, eight ruminally cannulated, crossbred heifers were utilized in a 4 × 4 Latin square to determine digestibility and ruminal fermentation characteristics of the diets from Exp. 2. Heifers were utilized in four consecutive 15-d periods. Final BW and ADG were similar (P = 0.37) between AL and LIM75, and greater (P ≤ 0.05) in LIM80 and LIM85 compared with AL. By design, dry matter intake was greater (P ≤ 0.01) in AL heifers compared to all 3 limit fed treatments. As a results feed conversion was improved by 30% (P ≤ 0.01) in limit fed heifers compared with AL and did not differ (P ≥ 0.20) among LIM75, LIM80, or LIM85. Dry matter digestibility was 10%, 5%, and 4% greater in among LIM75, LIM80, and LIM85, respectively, compared with AL. Organic matter, neutral fiber, and acid fiber digestibility were also greater in limit-fed treatments compared to AL. A treatment × hour interaction (P < 0.01) was observed for ruminal pH. Limit fed calves reached pH nadir earlier compared with AL with LIM75 being lowest, LIM80 intermediate, and LIM85 being greatest. Total ruminal VFA concentrations were unaffected by treatment (P = 0.34); however, there was a tendency (P = 0.08) for propionate concentrations to be intermediate and greater in LIM80 and LIM85 heifers, respectively, compared with AL and LIM75. Ruminal ammonia concentrations were greater (P < 0.01) in AL compared to limit fed treatments and experienced three different peak concentrations 2, 8, and 18 h post feeding compared with limit fed treatments singular peak 2 h post feeding (treatment × hour; P < 0.01). Based on our data in Exp 1, there is still variation in pH measured obtained via indwelling pH boli. Both MOON and SMAX experienced drift over time, however, during a simulated acidosis challenge MOON detected changes in pH similar to METER. Conversely, ruminal pH measurements over a 24 h period using SMAX were more closely related to METER. Based on results in EXP 2 and 3, limit feeding higher energy diets that include corn coproducts does not negatively influence growth performance or fermentation products. Subsequently, limit feeding improved total-tract digestibility and feed efficiency compared to a traditional receiving ration.
Keywords: Growing cattle; Limit feeding; Ruminal pH; Subacute ruminal acidosis